Echinatin attenuates acute lung injury and inflammatory responses via TAK1-MAPK/NF-κB and Keap1-Nrf2-HO-1 signaling pathways in macrophages - Luo, Liuling; Wang, Huan; Xiong, Jinrui; Chen, Xiaorui; Shen, Xiaofei; Zhang, Hai (PloS one, 2024)
Echinatin is an active ingredient in licorice, a traditional Chinese medicine used in the treatment of inflammatory disorders. However, the protective effect and underlying mechanism of echinatin against acute lung injury (ALI) is still unclear. Herein, we aimed to explore echinatin-mediated anti-inflammatory effects on lipopolysaccharide (LPS)-stimulated ALI and its molecular mechanisms in macrophages. In vitro , echinatin markedly decreased the levels of nitric oxide (NO) and prostaglandin E2 (PGE 2 ) in LPS-stimulated murine MH-S alveolar macrophages and RAW264.7 macrophages by suppressing inducible nitric oxide synthase and cyclooxygenase-2 (COX-2) expression. Furthermore, echinatin reduced LPS-induced mRNA expression and release of interleukin-1β (IL-1β) and IL-6 in RAW264.7 cells. Western blotting and CETSA showed that echinatin repressed LPS-induced activation of mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF-κB) pathways through targeting transforming growth factor-beta-activated kinase 1 (TAK1). Furthermore, echinatin directly interacted with Kelch-like ECH-associated protein 1 (Keap1) and activated the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway to enhance heme oxygenase-1 (HO-1) expression. In vivo , echinatin ameliorated LPS-induced lung inflammatory injury, and reduced production of IL-1β and IL-6. These findings demonstrated that echinatin exerted anti-inflammatory effects in vitro and in vivo , via blocking the TAK1-MAPK/NF-κB pathway and activating the Keap1-Nrf2-HO-1 pathway.